Pelatihan Microsoft Office Sebagai Upaya Peningkatan Kemampuan Aparat Desa Dalam Pelaksanaan Tugas Administrasi Pemerintahan Desa - Rachyu Purbowati; Mardi Astutik (STIE PGRI Dewantara Jombang, 2017)
AbstractVillage administration as the smallest government in the community, is required to provide excellent service to the community. Village officials are expected to be able to work quickly, effectively and efficiently for the community and well served. This needs to be supported by the ability of human resources to be able to take advantage of existing technology that is computer to accelerate and simplify its work. This training and mentoring activity was held in Plosogeneng Kecamtan Jombang Village in July 2017. This type of activity is in the form of Microsoft Office training for village officials. Implementation of the occult is a team of writers assisted by a staff STIE PGRI Dewantara Jombang.From the results of the activity, the benefits of improving the administrative capacity of village officials are very helpful in completing administrative tasks in the village.Keywords: Training, Microsoft Office, Administration, Village